Kontrol Frekuensi Wind-Diesel Menggunakan Hibrid Kontroller PID-BA-ANFIS - Machrus Ali; Miftachul Ulum (Universitas Islam Lamongan, 2020)
The wind diesel system is greatly influenced by the wind speed and which is then combined with the diesel engine. Optimization of wind-diesel systems is needed to get good frequency quality and optimal power. The optimal setting of the gain and time constant on the Load Frequency Control (LFC) causes the frequency stability to be weak. In practice, the wind-diesel system is controlled by a PID controller and Fuzzy Logic Controller. At present the gain value setting of the PID is still in the conventional method, so it is difficult to get the optimal value. In this study the control design is applied by using the Smart Method in finding the optimum Proportional Integral Derivative (PID) based on Bat Algorithm (BA). For comparison, the method is used without a control method, conventional PID method, PID auto tune matlab method, PID-BA method, and PID-BA-ANFIS. Wind-diesel modeling uses the transfer function of wind turbine and diesel diagrams. From the results of research that has been done shows that the smallest undershoot on PID-BA-ANFIS, the smallest overshot on PID-BA-ANFIS, and the fastest settling time is equal to PID-BA-ANFIS. This research can later be continued using other artificial intelligence methods.